Triglyceride glucose index is associated with cerebral small vessel disease burden and cognitive impairment in elderly patients with type 2 diabetes mellitus - Teng, Zhenjie; Feng, Jing; Dong, Yanhong; Xu, Jing; Jiang, Xin; Chen, Huifang; Qi, Qianqian; Li, Rui; Chen, Weihong; Lv, Peiyuan (Frontiers in Endocrinology, 2022)
Objective: To investigate the relations of Triglyceride glucose (TyG) index with cerebral small vessel disease (CSVD) burden and cognitive function in aged patients with type 2 diabetes mellitus (T2DM). Methods: A total of 308 elderly patients with T2DM were included in this retrospective study. The standardized Chinese version of Mini-Mental State Examination was used to assess cognitive function. The total CSVD burden score was assessed by combining four imaging markers of CSVD, including the presence of white matter hyperintensity, cerebral microbleeds in the deep, lacunes and enlarged perivascular spaces in the basal ganglia. The TyG index was calculated as the formula of ln [fasting triglyceride (mg/dl) × fasting plasma glucose (mg/dl)/2]. We used logistic regression analysis and mediation analysis to investigate the relations of TyG index with CSVD and cognitive function. Results: Multivariate binary logistic regression analysis showed that increased TyG index (OR: 2.241; 95% Confidence Interval(CI): 1.439 to 3.490; P <0.001), or severe CSVD burden (OR: 2.198; 95% CI: 1.283 to 3.763; P = 0.004) was associated with an increased risk of cognitive impairment in elderly patients with T2DM after adjusting for potential confounders. In addition, TyG index was an independent risk factor of severe CSVD burden (OR: 1.472; 95% CI: 1.003 to 2.160; P = 0.048) after controlling for potential confounders. Compared with the lowest TyG index tertile, the multivariable-adjusted OR of the highest tertile was 3.298 (95% CI: 1.685 to 6.452; P for trend <0.001) for cognitive impairment, 1.933 (95% CI: 1.010 to 3.698; P for trend = 0.047) for severe CSVD burden. Mediation analysis found a significant moderating effect of the severe CSVD burden on the association between higher TyG index levels and cognitive impairment. Conclusions: The increased TyG index is an independent risk factor for cognitive impairment and severe CSVD burden in clinical practice. A proportion of the effect of increased TyG index on cognitive impairment may be due to the aggravation of CSVD burden.